The Animal Models for Hemorrhage and Thrombosis in the Neonate - Kisker, C Thomas (Thrombosis and Haemostasis, 1987)
Animal models have added significantly to our understanding of adult hemorrhagic and thrombotic diseases. Few models, however, have been developed for studies of the hemostatic disorders in the fetus and newborn. This report reviews the current information on animal models of fetal and neonatal hemostasis. The requirements of a relevant model are addressed and previous studies using fetal and neonatal animal models are reviewed. A recommendation of a single animal for all studies of fetal and neonatal hemostasis is not possible. However, the lamb has been the most frequently studied and appears to provide relevant information regarding normal development and the factors which may adversely influence hemostasis in the fetus and newborn.
Keywords: Animal models; Hemorrhage; Thrombosis; Neonate